Cultural adaptation challenges and strategies during study abroad: New Zealand students in China. Issue 4 (2nd October 2021) - Gong, Yang (Frank); Gao, Xuesong (Andy); Li, Michael; Lai, Chun
ABSTRACT: The rising popularity of the Chinese language as a subject for study has motivated research on international students' cultural adaptation and language learning during periods of study abroad in China. This inquiry examined the challenges that a group of New Zealand students encountered and the strategic responses they adopted in relation to cultural adaptation in China. In the inquiry, we encouraged 15 participants to write reflective journals and conducted group interviews to explore their experiences. The analysis revealed the variety of challenges that the participants faced, including language-based, lifestyle, and academic challenges as well as sociocultural and psychological ones. In response to these challenges, the participants adopted diverse strategic efforts to achieve cognitive, affective, and skill development in facilitating their communication practices with local Chinese people. These findings suggest that language educators need to revise traditional pedagogical approaches so that new pedagogical activities can be developed to promote study abroad students' communication competence, and counselling services should be provided to support their cultural adaptation and language learning.